A simple spot weld joint finite element model for vibration analysis - Kong, Y.; Khandokera, N.; Lee, Vincent; Islamc, S. (2018)
© 2018 Trans Tech Publications, Switzerland. Resistance spot welding is one of the commonly used structural joining processes in sheet metal structures. This paper presents the study of vibration characteristics of a spot-welded sheet metal coupon with a simple finite element model. The finite element spot weld nugget was modelled with Spider Configuration (SC) using commercial finite element code ABAQUS. Analytically the spot welded sheet metal coupon was modeled as a free-free Euler Bernoulli beam. Comparison was made for both natural frequencies and mode shapes of the first three bending modes between finite element model and analytical model. It was found that the simple finite element model was able to predict the spot weld joint vibration characteristics with a minimum of 0.35% and a maximum of 7.3% error.